2018
DOI: 10.1016/j.jpsychires.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in unaffected adolescent biological relatives of schizophrenia patients

Abstract: Impulsivity is associated with schizophrenia risk, and its severity increases with greater familial relatedness to the schizophrenia proband. Additional studies are needed to understand the role impulsivity may play in mediating schizophrenia susceptibility during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…This is interesting because lack of perseverance has also been associated with several domains of psychopathology including depression, borderline personality traits, disordered eating, alcohol and substance use 51 . While lack of perseverance has been associated with an increased vulnerability for the development of schizophrenia 52 , other research indicates no association between lack of perseverance and a diagnosis of schizophrenia 53 . The current study does not provide evidence as to the relationship between lack of perseverance and DSM diagnoses such as major depressive disorder or schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting because lack of perseverance has also been associated with several domains of psychopathology including depression, borderline personality traits, disordered eating, alcohol and substance use 51 . While lack of perseverance has been associated with an increased vulnerability for the development of schizophrenia 52 , other research indicates no association between lack of perseverance and a diagnosis of schizophrenia 53 . The current study does not provide evidence as to the relationship between lack of perseverance and DSM diagnoses such as major depressive disorder or schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…When interaction effects were significant, the simple main effects test was conducted with Bonferroni corrections. Since impulsivity has been shown to be related to delay discounting (Ainslie, 1975;Hoe et al, 2018), scores on the BIS and the BDI were further entered into the MANOVA and the ANOVA as a covariate for further analysis independently. The k all values were calculated in MATLAB R2017b (MathWorks Inc.; https://www.mathworks.com).…”
Section: Discussionmentioning
confidence: 99%
“…The results from Li et al (2016b) and the present study both suggest that negative schizotypy may be strongly associated with alterations in anticipatory reward processing. However, previous studies investigating delay discounting in patients with schizophrenia and their relatives have produced mixed results, with smoking status reported as a confounding factor (Heerey et al, 2011;Hoe et al, 2018;Yu et al, 2017;MacKillop and Tidey, 2011). In our study, we have carefully matched the smoking status between the two groups of participants to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, a proactive coping style is often associated with impairments in attention and cognitive flexibility, as well as heightened impulsivity (for a review see Coppens et al, 2010). These traits have in turn been associated with schizophrenia in patients (Brown et al, 2018; Ho et al, 2018). Thus, using both psychometric impulsivity scales and the delay discounting task (a measure of action planning and impulse control in which higher rates of reward discounting, due to the preference of smaller and immediate rewards over delayed and larger ones, reflect enhanced impulsivity), it has been shown that impulsivity measures are positively associated in a consistent manner with schizophrenia, schizoaffective disorder, and schizophrenia risk in unaffected biological relatives of patients (Ahn et al, 2011; Brown et al, 2018; Ho et al, 2018).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%